China's human resources for maternal and child health: a national sampling survey. Issue 1 (June 2015) - Ren, Zhenghong; Song, Peige; Theodoratou, Evropi; Guo, Sufang; An, Lin
Abstract Background In order to achieve the Millennium Development Goals (MDG) 4 and 5, the Chinese Government has invested greatly in improving maternal and child health (MCH) with impressive results. However, one of the most important barriers for further improvement is the uneven distribution of MCH human resources. There is little information about the distribution, quantity and capacity of the Chinese MCH human resources and we sought to investigate this. Methods Cities at prefectural level were selected by random cluster sampling. All medical and health institutions providing MCH-related services in the sampled areas were investigated using a structured questionnaire. The data were weighted based on the proportion of the sampled districts/cities. Amount, proportions and numbers per 10, 000 population of MCH human resources were estimated in order to reveal the quantity of the Chinese MCH human resources. The capacity of MCH human resources was evaluated by analyzing data on the education level and professional skills of the staff. Results There were 77, 248 MCH workers in our investigated institutions in 2010. In general, 67.6 % and 71.9 % of the women's and children's health care professionals had an associate degree or higher, whereas around 30 % had only high-school or lower degrees. More than 40 % of the women's health workers were capable of providing skilled birth attendance, but these proportions varied between different institutions and locations. Conclusions Evidence from this study highlights that Chinese MCH human resources are not in shortage in the national level. However, the quantity and capacity of MCH human resources are not evenly distributed among different institutions and locations. Finally there is a need in the improvement of the MCH services by improving the quality of MCH human resources.